Antioxidant and genoprotective activity of selected cucurbitaceae seed extracts and LC–ESIMS/MS identification of phenolic components. (15th May 2016) - Yasir, Muhammad; Sultana, Bushra; Nigam, Poonam Singh; Owusu-Apenten, Richard
Highlights: Cucurbitaceae seeds are novel sources of flavonol glycosides. Cucurbitaceae seeds are sources of phenolic acid and esters. Acidification improves aqueous methanol recovery of cucurbitaceae glycosides. Extracts from Cucurbitaceae seeds possess antioxidant and genoprotective activity. Abstract: Cucurbitaceae are one of most widely used plant species for human food but lesser known members have not been examined for bioactive components. The purpose of this study was to evaluate the antioxidant and genoprotective activities from three cucurbitaceae seeds extracts and to identify phenolic components by LC–ESIMS/MS analysis. From the results, the yield of seeds extract was 20–41% (w/w) and samples had 16–40% total phenols as gallic acid equivalents (GAE). Compared with methanol solvent, using acidified methanol led to increased extraction yield by 1.4 to 10-fold, higher phenolic content (149.5 ± 1.2 to 396.4 ± 1.9 mg GAE/g), higher DPPH radical quenching and enhanced genoprotective activity using the pBR322 plasmid assay. LC–ESI-MS/MS analysis led to identification of 14–17 components, based on authentic standards and comparison with literature reports, as mainly phenolic acids and esters, flavonol glycosides. This may be the first mass spectrometric profiling of polyphenol components from cucurbitaceae seeds.